DEVELOPMENT STRUCTURE AND METHOD FOR OBTAINING A DOUBLE-SIDED PLUSH WEAVING ON THE BASIS OF A DOUBLE-WINDOW JERSEY (Academia Science Repository, 2023)
The issues of expanding the range and improving the quality of plush knitwear, creating new structures and developing effective methods of knitting knitwear with optimal parameters are currently being dealt with by many researchers both in our country and abroad. Knitwear produced from ground threads by any main, derivative or patterned weave with knitting additional threads or bundles of staple fibers into the ground, forming increased platinum arcs or pile broaches, is called knitted plush weave.